Oxidation of nucleic acids: Chemistry of pyrene quinone (PQ 1) and development of dihydrodioxins (DHD 2) as DNA photooxidizing agents - Alsulami, Rabah N.; Sallans, Larry; Khisamutdinov, Emil F.; Pandey, U.; Glusac, Ksenija; Wilson, R. Marshall (Journal of photochemistry and photobiology. A, Chemistry., 2019)
[Display omitted] •Pyrene quinone photochemistry.•Dipyridinium dihydrodioxin photochemistry.•Photochemical damage to DNA.•Mass spectrometry of DNA damage.•Atomic force microscopy of DNA damage. Pyrene-4,5-dione (pyrene quinone, PQ 1) is a polycyclic aromatic hydrocarbon (PAH), a planar group and DNA-cutting functionality that can cause cytotoxic, mutagenic, and carcinogenic damage to DNA and can encourage cancers in humans. It is extensively accepted that PAHs require metabolic activation in order to exert their biological activities, including carcinogenicity. Upon entering the cell PAHs are either metabolized into diol epoxides, quinones, or free-radical intermediates, all of which can react with cellular DNA to produce PAH-DNA covalent adducts and cause other forms of DNA damage. We have studied the binding and photo-reaction of PQ 1 with herring sperm (HS) DNA in order to see if it binds to the DNA. PQ 1 alone does not bind to herring sperm DNA, even though it might form hydrogen bonds with bases. In addition, PQ 1 alone does not linearized super-coiled ΦX174 plasmid DNA. Therefore, PQ 1 alone does not have the capability to photochemically cleave and/or damages DNA duplexes directly. We attribute this lack of reactivity to the low solubility of PQ 1 in water, since when it is masked with a water solubilizing group (dipyridinium dihydrodioxin), DHD 2, it is very effective in causing DNA damage. Electrochemical results indicate that the reduction potential of the first electron donated to PQ 1 in acetonitrile has E0red = −0.052 V vs. NHE, and converts it to the semiquinone radical anion. Thus, the Gibbs free energy (ΔG0) of the electron transfer to the excited state of PQ 1 in DNA is roughly estimated using the Rehm–Weller equation to have ΔG0 = −33.536 kcal/mol, which indicates the electron transfer can happen spontaneously from adenine to the photoexcited PQ 1. These results strongly suggest, and are consistent with the hypothesis, that PQ 1 cleaves and/or damages DNA duplexes at Gs or As when it is intercalated between base pairs. DNA–DHD 2 interactions have previously been investigated by transient absorption spectroscopy which indicates that PQ 1 is photochemically released into the base pair stacks where it can photochemically triggers the further release of PQ 1 and cause extensive DNA damage. Thus the photochemical release of PQ 1 from DHD 2 is autocatalytic, which makes this system a very effective DNA oxidizing system. The nature of this DNA damage has been investigated by mass spectroscopy using electrospray ionization. In this work, experiments using DNA with known sequences of nucleotides such as: A7 + DHD 2, A7 + PQ 1, ds (T7A7) + DHD 2, and ds (T7A7) + PQ 1, were investigated. DHD+22-2BF4− photochemically damages the DNA and the generated PQ 1 and dipyridinium stilbene become attached to the DNA bases at different positions. Furthermore, atomic force microscopy of the plasmid ΦX174 photochemically damaged with DHD 2 indicates that the DNA strands become extensively crosslinked together forming aggregated DNA that would not be subject to repair.